Unusual location of cutaneous alternariosis in an immunocompetent patient. (2022) - Jebari, Maroua; Mtibaa, Latifa; Abid, Rym; Hannechi, Souha; Souid, Hana; Battikh, Riadh; Louzir, Bassem; Jemli, Boutheina
Abstract: Alternaria is a dematiaceous fungus ubiquitously found in nature. It can cause infections, especially in immunocompromised patients. We report a periorbital location of Alternaria infection in an immunocompetent woman with a confusing clinical presentation. The diagnosis was confirmed by a cutaneous biopsy of the cheek. PCR sequencing identified Aternaria alternata species. The evolution was fatal despite antifungal treatment.